Notaries Modern-Age Mediators? Some Reflections on the Role of the Notary in Austrian Lombardy (18th Century) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
Far from representing a group of anonymous document editors, the Lombard notaries of the 18th Century reveal themselves to be endowed with a marked versatility, which allowed them to wedge themselves into the various institutional sectors in which the peripheral power of the ancient regime was articulated and to interact with the population carrying out, at least at certain levels and under certain conditions, a role of mediation not only juridical but also social and cultural, guiding and directing the relationships, sometimes intricate, between private individuals, as well as between ecclesiastical bodies and society.
Keywords: Notaries; Mediators; Lombardy; 18th Century